A Comparative Study of The Attitude of Hindu and Muslim Women, Their Educational Level and Social Change in Sitamarhi District - Anand, Amit; Khan, Masood Alam; Hussain, Zakir (Eduvest - Journal of Universal Studies, 2023)
Education is an important factor in any society, with the help of which both direction and condition of the society change. In ancient India, traditional education was imparted through religious institutions. In the Vedic period, the status of women was very good and high, women were able to work side-by-side with their husbands and could decide for their future life. She had the right over the property of her father and husband. Swayamvar system was the strong foundation of the social status of women. The study aims to find out the effect of revolution and progress in education due to social change in present times on Hindu and Muslim Women. In the study descriptive research design has been used. It is clear from the result obtained from the study of the data that the social status of Hindu and Muslim women there is a general level of attitude towards change. Women with higher education expressed less attitude and women with less education expressed more attitude. This research would be much useful in future for study related to Hindu and Muslim women in different walks of life.